Strategi Promosi Produk Pembiayaan UGT Modal Pertanian Barokah pada BMT UGT Sidogiri Dadapan Bondowoso: Promotion Strategy for UGT Financing Products, Barokah Agricultural Capital, at BMT UGT Sidogiri Dadapan Bondowoso - Anam, Khoirul; Sulistiyo, Agung Budi; Subagio, N. Ari (IJABAH: Indonesian Journal of Sharia Economics, Business, and Halal Studies, 2023)
This study aims to determine the promotion strategy used by BMT UGT Sidogiri in increasing the financing products for barokah agricultural capital at BMT UGT Sidogiri Dadapan Bondowoso. This type of research uses a case study approach based on in-depth investigation. This research is a qualitative descriptive research with data collection methods through observation, interviews, and documentation. The results of the research are based on the results of interviews related to the promotion strategy used by BMT UGT Sidogiri to increase the product of barokah agricultural capital financing, namely; 1) direct face-to-face/personal selling where members of the BMT UGT Sidogiri go directly by way of friendly relations in order to market products owned by BMT and introduce BMT to the surrounding community. 2) BMT UGT Sidogiri carries out promotions through social media such as WA (whatsapp), sms, Facebook, and uses brochures.